PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022) - Moniaga, Reggina Angela; Tanusdjaja, Hendang (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to empirically prove the effect of profitability, leverage, and firm size on firm value. The purposive sampling method was used to collect data in this study. In this study, the subjects used were property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Secondary data was used in this study with a total sample of 32 companies and 128 sample data. This study uses the SPSS 26 program for data processing. From the results obtained in this study, the two independent variables namely profitability and leverage have a significant positive effect on firm value. Meanwhile, firm size has no significant negative effect on firm value.